(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines various methods of language teaching, including Grammar-Translation, Direct Method, Audio-Lingual, Communicative Language Teaching, Task-Based Language Teaching, and innovative approaches like Silent Way and Suggestopedia. It highlights the principles, techniques, and advantages of each method, and emphasizes the importance of selecting appropriate methods based on learners’ needs and goals.